PSYCHOGRAPHIC CHARACTERISTICS INFLUENCING CONSUMER BEHAVIOUR TOWARDS ONLINE PURCHASE INTENTION: A STUDY ON GENDER DIFFERENCES - Rahim, Hardy Loh; Rosly, Hardi Emrie (Journal of Technology Management and Business, 2014)
E-commerce has emerged as an important method of business. With nearly 2.5 trillion internet users worldwide and surpassed USD1 trillion sales in 2012, it is essential to understand the behavior of the online shoppers. Previous studies have explored the relationship of customer innovativeness, market mavenism, shopping enjoyment, shopping orientation towards online purchase intention. Thus this study would like to understand further on the gender differences upon the psychographic characteristics that influence online purchase intention. A survey technique using national sample of online shoppers resulted in 174 valid responses. Analysis using SPSS was done to investigate the difference between genders in terms of the variables involved. This paper analyzed and demonstrates empirically how consumer psychographic characteristics that affect the online purchase intention differ from gender perspective.